Steady method to retrieve effective electromagnetic parameters of bianisotropic metamaterials at one incident direction in the terahertz region. (1st October 2017) - Zhao, Jingyin; Jing, Xufeng; Wang, Weimin; Tian, Ying; Zhu, Dongshuo; Shi, Guohua
Highlights: We propose a straightway and steady method to extract the effective parameters. The method is verified by the isotropic and the bianisotropic metamaterials. The electric coupling to magnetic resonance is verified by extracted parameters. Abstract: We propose a steady method to extract the effective constitutive parameters of a slab of bianisotropic split-ring resonator metamaterial from reflection and transmission coefficients. The effective permittivity, permeability and magnetoelectric coupling coefficient of bianisotropic metamaterial can be simply retrieved by our derived analytical inversion equations. In our retrieval method, the transmission and reflection coefficients in only one direction of wave propagation were applied. The method was verified by the retrieval constitutive parameters for different metamaterials, among which one is isotropic structure and the other one is bianisotropic metamaterial. The intrinsic difference between the normal isotropic metamaterial and the bianisotropic metamaterial was evidently revealed. The resonant characteristic of the split ring resonator metamaterial including electric coupling to magnetic resonance was verified by the extracted effective constitutive parameters. The proposed method can be effectively applied in investigation of bianisotropic performance of metamaterials.